Assessing Maternal Length of Stay and Its Associated Factors at Obstetrics Ward of the Korle Bu Teaching Hospital - Brocke, T.N.A. (University of Ghana, 2023)
Background: Obstetric care refers to the care provided to patients during the antenatal, intrapartum, and postpartum periods. This is the most common and costly type of hospital care for all payers and healthcare institutions in most parts of the world. According to the World Health Organization (WHO) all women should remain admitted for at least 24 hours after birth. But there is no consensus around appropriate length of stay. Method: The study design employed was an observational retrospective study. 2142 mothers were included in the study. The data were coded, cleaned with Windows Excel 2016 and analysed using Stata IC (Version17.0). Only variables with missing values of 5% or less were used for the regression analysis. Continuous and categorical variables were summarized using means and frequency distribution respectively. Chi square was used to test the association between the variables. Bivariate and multivariate logistic regression analysis were done to determine the strength of association between the dependent and independent variables. Results: Age was not significantly associated with LOS (AOR=1.10, 95% CI=0.98-1.03, p=0.68). Women with three pregnancies still had a lower risk of longer LOS compared to those with one pregnancy (AOR=0.55, 95% CI=0.38-0.80, p=0.002). Married women and cohabiting women still had a lower risk of longer LOS compared to single women (AOR=0.54, 95% CI=0.34-0.88, p=0.01 and AOR=0.44, 95% CI=0.27-0.64, p=0.00*, respectively). Women with secondary education still had a higher risk of longer LOS compared to those with no education (AOR=2.09, 95% CI=1.20 3.63, p=0.00*) Recommendation: Healthcare providers should work towards improving the quality of care for obstetric patients, particularly those who are at a higher risk of longer LOS.
MPH.
Keywords: Obstetric care; antenatal; intrapartum; postpartum